1996
DOI: 10.2466/pms.1996.82.3c.1171
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers' Socialization as Consumers of Clothing and Recognition of Symbolism

Abstract: To investigate the relative influence developmental and environmental factors have on young children's socialization as consumers 45 verbal preschool children (2 to 5 years) were administered a verbal questionnaire to assess their recognition of 8 consumer symbols. The children's mothers completed a questionnaire concerning their perceptions of their children's identity and the roles media, peers, and siblings play in children's preferences for clothing symbols. Correlations and multiple regression confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…The aim of this first study is to assess levels of brand recognition in children aged 3 to 5 years. Past research has shown that preschool children are capable of recognizing brands, and it has been suggested that 3‐ and 4‐year‐olds can readily name brands such as McDonald's, M&M's, and Oreos (e.g., Derscheid, Kwon, & Fang, 1996; Haynes et al, 1993). Note that these brands all belong to similar product categories (fast food and snacks).…”
Section: Brand Recognition Studymentioning
confidence: 99%
“…The aim of this first study is to assess levels of brand recognition in children aged 3 to 5 years. Past research has shown that preschool children are capable of recognizing brands, and it has been suggested that 3‐ and 4‐year‐olds can readily name brands such as McDonald's, M&M's, and Oreos (e.g., Derscheid, Kwon, & Fang, 1996; Haynes et al, 1993). Note that these brands all belong to similar product categories (fast food and snacks).…”
Section: Brand Recognition Studymentioning
confidence: 99%
“…Taking the first prerequisite, the evidence indicates that children can recognize familiar brand names and brand characters at an early age, at least by 3 or 4 years of age (Derscheid, Kwon, & Fang, 1996;Haynes, Burts, Dukes, & Cloud, 1993). At this time, children's awareness of brands is typically developed enough that they even request products by brand names, such as McDonald's ® , M&M's ® , and Oreos ® .…”
Section: Development Of Conceptual Brand Meaningsmentioning
confidence: 99%
“…1 One of the goals of marketing is branding to encourage children to recognize and differentiate particular products and logos. By 2 years of age, children may have beliefs about specific brands, 4 and 2-to 6-year-olds can recognize familiar brand names, packaging, logos, and characters and associate them with products, [5][6][7][8] especially if the brands use salient features such as bright colors, pictures, and cartoon characters. 8 By middle childhood, most children can name multiple brands of child-oriented products.…”
mentioning
confidence: 99%